Analisis Torsi Sepeda Motor Vixion New 2013 Menggunakan Final Drive Gear Ukuran 13, 14 dan 15 - Ahmadi, Syukri; Mukhnizar, Mukhnizar; Abu , Risal; Selviyanty, Veny; Afdal, Afdal (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Motorcycles are vehicles that have quite high economic value when compared to other vehicles. Motorcycles are made up of several constituent components, one of which is the use of final gear. The purpose of this study was to determine the amount of torque and the ratio of torque produced from the final gear size 13,14,15 on the new 2013 vixion motor. From the data obtained, the maximum torque when using the final gear size 13 = 15.24 Nm at a speed of 7.05 rpm. 14 = 15.49 Nm at 7.33 rpm and 15 = 15.91 Nm at 6.83 rpm. While the difference in the ratio of torque produced by the final gear (standard) size 13 and size 14, the difference in value = 0.22 Nm, the final gear size 14 is larger, the difference in the torque ratio between size 14 and size 15, the difference in value = 0.35, is greater than 15 size 14, the difference in the torque ratio between size 15 and size 13 is the difference in value = 0.57 Nm, which is 15 greater than size 13